Esophageal Bronchus: A Case Report - Vidyanand Deshpande; Mridul Tantia (EL-Med-Pub, 2019)
Esophageal bronchus has communication with esophagus instead of trachea. We report a case of esophageal bronchus in a 12-day-old term neonate who presented with respiratory distress. Chest radiograph showed opacification in parts of lower lobe of right lung. Computed tomography (CT) revealed an abnormal bronchus arising from the lower third of esophagus and communicating with affected part of right lung. Subsequently, a right posterolateral thoracotomy was done, esophageal bronchus was divided and the affected collapsed part of lung was excised. Post-operative recovery was uneventful.